Sustainable Livelihoods through Natural and Environmental Resource Empowerment: A Case Study of Afdeling II Bukit Village, Birem Bayeun, East Aceh, Indonesia - Alfian Muhammad; Muhammad Amin; Safwan Kamal; Fakhrizal Mustafa; Anis Kurlillah; Nanda Safarida; Shelly Midesia; Iksal Maulana; Danang Al Qadri; Fathia Mahirah; Fadilla Zulkarnaini; Nur Suciarni; Faisal Yahya (SEURAYA Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program was conducted in Afdeling II Bukit Village, Birem Bayeun District, East Aceh Regency, aiming to empower the community through the Asset-Based Community Development (ABCD) approach. The main issue identified was the underutilization of natural and environmental resources as productive economic assets. The activities were carried out through several stages, including local asset mapping, training on processing palm fronds into value-added products, training on utilizing family medicinal plants into herbal drinks, Focus Group Discussions (FGDs), and continuous mentoring. The implementation emphasized community participation, collaboration with village authorities, and the application of simple digital technologies to enhance product marketing. The results showed an increase in community skills in managing local resources, the formation of asset-based business groups, and greater awareness of economic independence based on local potential. In conclusion, the ABCD approach proved effective in fostering rural economic self-reliance through the strengthening of local assets and continuous mentoring integrated with digital innovation.